DIGITIZATION AND INTELLIGENT MANAGEMENT SYSTEMS IN TRANSPORT: AN OVERVIEW OF PROBLEMS AND SOLUTIONS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The implementation of intelligent transport systems /ITS - Intelligent Transport/ in the transport sector is one of the first tasks in the development of information and communication technologies /Information and Communication Technologies - ICT/. In essence, it is an actual task and means creating and processing the information flows and data in real time to locate and manage the vehicles, infrastructure and traffic in order to improve the mobility and the quality of the transport services offered. This article aims to give a modern view of digitalization of technological and business processes, as well as the development of ITS in the field of the transport sector. Special emphasis is given to modern problems and solutions in the digitization and implementation of these information systems. with a view to their effective and safe use, traffic and mobility management, improving the efficiency and quality of the service, as well as the impact on the ecology, etc.